2007
DOI: 10.2174/156720107782151250
|View full text |Cite
|
Sign up to set email alerts
|

Niosomal Gel for Site-Specific Sustained Delivery of Anti-Arthritic Drug: In Vitro-In Vivo Evaluation

Abstract: Celecoxib, a selective COX-2 inhibitor is commonly used in the treatment of arthritis. Recently, cardiotoxic effects associated with conventional modes of delivery of celecoxib have made it pertinent to develop alternate dosage forms capable of selectively delivering the drug topically to affected joints. The aim of the present study was to prepare and characterize niosomal gel formulation for sustained and site-specific delivery of celecoxib. Celecoxib loaded niosomes were prepared and characterized in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The skin was removed, cut into small pieces, fixed, microtomed (5 μm thickness), and sections were fixed on glass slide. These sections were stained with eosin-hematoxylin and observed under optical microscope (DX 31, Olympus, Tokyo, Japan) for integrity and structural changes of epidermis (22).…”
Section: Skin Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin was removed, cut into small pieces, fixed, microtomed (5 μm thickness), and sections were fixed on glass slide. These sections were stained with eosin-hematoxylin and observed under optical microscope (DX 31, Olympus, Tokyo, Japan) for integrity and structural changes of epidermis (22).…”
Section: Skin Toxicity Studiesmentioning
confidence: 99%
“…Phosphatidylcholine is used as bilayer forming agent. Niosomes was used as control and prepared by optimized composition as reported by our group (22). Niosomes consist of non-ionic surfactant as bilayer forming agent along with cholesterol and PC as stabilizing agent.…”
Section: Preparation Of Elastic Liposomal Formulationsmentioning
confidence: 99%
“…[13][14][15][16][17][18] Microemulsions are thermodynamically stable transparent (translucent) dispersions of oil and water stabilized by an interfacial film of surfactant and cosurfactant molecules having the droplet size less than 100 nm. [13] Studies have shown that microemulsion formulations possess improved transdermal and dermal delivery properties in vitro and in vivo [13][14][15][16][17][18] over other colloidal drug delivery systems that include self-microemulsifying drug delivery systems, [19] niosomes, [20] nanoemulsions, [21] solid dispersions, [22] cyclodextrin complex, [23,24] aerosols, [25] polymeric dispersions. [26] The aim of the present study was to prepare and characterize microemulsions formulation for sustained and site-specific delivery of celecoxib.…”
Section: Introductionmentioning
confidence: 99%
“…Their percutaneous absorption across exercised rat skin showed greater flux compared with the nonelastic niosomes. The application of pMEL34-loaded elastic cationic niosomes in melanoma cell lines gave four times increase in tyrosinase gene expression compared with the free and the plasmid in nonelastic niosomes which lead to efficient topical delivery in vitiligo therapy [103]. Tretinoin (vitamin A metabolite), is topically applied for the treatment of skin diseases such as acne, psoriasis, and photoaging.…”
Section: Niosomes For Transdermal Delivery Of Drugsmentioning
confidence: 99%